Sepse por Staphylococus aureus resistente à meticilina adquirida na comunidade no sul do Brasil - Gelatti, Luciane Cristina (2009)
Methicillin-resistant Staphylococcus aureus was initially described as a typical microorganism acquired in nosocomial infections. However, over recent years, community-acquired methicillin-resistant Staphylococcus aureus has been a cause of skin and soft-tissue infections. Serious infections such as pneumonia and sepsis can also occur. This report describes a case of sepsis in a child that was complicated by pneumonia secondary to soft tissue lesions that were due to community-acquired methicillin-resistant Staphylococcus aureus in southern Brazil. The patient was attended at the Emergency Unit with a history of injury caused by lower-limb trauma that evolved to cellulitis, pneumonia and sepsis.